Manipulating Transfer and Separation of Photocarriers in Monolayer WS2 via CdSe Quantum Dot Doping - Feng, Qiushi; Li, Yuanzheng; Gao, Fei; Sun, Ying; Yan, Jiaxu; Liu, Weizhen; Xu, Haiyang; Liu, Yichun (ACS photonics, 2020)
Flexibly manipulating optical and electrical properties of 2D materials is of great importance to extend their functional applications in the advanced optoelectronic field. Herein, a type II 2D/0D hybrid heterostructure is facilely fabricated by spin-coating CdSe quantum dots (CdSe-QDs) onto monolayer WS2 (1L-WS2) flakes, and improved fluorescence emission and electron density of 1L-WS2 have been achieved through effective CdSe-QDs doping. The interfacial charge behavior is explored via X-ray photoelectron spectroscopy, scanning Kelvin probe force microscopy studies, and time-resolved photoluminescence measurements, proving the charge transfer from QDs to 1L-WS2 in these heterostructures. Furthermore, the photocurrent of a photodetector based on this hybrid heterostructure increases significantly due to efficient and fast separation and collection of photocarriers, verifying the validity of our proposed carrier dynamic model. The current work proposes a convenient strategy for tuning the photonic and electronic properties of 2D semiconducting materials, which may pave the way for developing new-type optoelectronic devices based on these newly emerging 2D materials and heterostructures.